2008
DOI: 10.1111/j.1469-0691.2008.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of drug-resistant Mycobacterium tuberculosis isolates collected in central Poland

Abstract: In total, 48 Mycobacterium tuberculosis clinical isolates from 48 patients with drug-resistant pulmonary tuberculosis (TB) in central Poland during 2004 were analysed by spoligotyping and IS6110-Mtb1/Mtb2 PCR. Twelve (25%) isolates were clustered by spoligotyping in combination with IS6110-Mtb1/Mtb2 PCR. Patients from whom these isolates were obtained were assumed to have developed TB as a result of recent transmission. Spoligotyping, used alone, overestimated the number of clustered isolates. However, combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Third, the phylogenetic analysis revealed that the two most prevalent clades among MDR and INH-resistant M. tuberculosis strains were T and Haarlem, representing 46% and 80% of these groups, respectively. These results corroborate previous observations on the predominance of the T and Haarlem genotypes in the epidemiology of drug-resistant TB in Poland (5,38). Furthermore, the presence of the T and Haarlem genotype isolates in such high proportions is consistent with the general features of the European population of M. tuberculosis.…”
supporting
confidence: 83%
“…Third, the phylogenetic analysis revealed that the two most prevalent clades among MDR and INH-resistant M. tuberculosis strains were T and Haarlem, representing 46% and 80% of these groups, respectively. These results corroborate previous observations on the predominance of the T and Haarlem genotypes in the epidemiology of drug-resistant TB in Poland (5,38). Furthermore, the presence of the T and Haarlem genotype isolates in such high proportions is consistent with the general features of the European population of M. tuberculosis.…”
supporting
confidence: 83%
“…This could be further supported by the fact that the same three types were found to be dominant in two previous spoligotyping studies in Poland (1,17). This observation indicates the continuing activity of these genotypes in the country.…”
supporting
confidence: 69%
“…The calculated discriminatory power of this method was higher than those of spoligotyping and MIRU-VNTR typing and almost equivalent to that of IS6110-RFLP typing (406)(407)(408).…”
Section: Methods Based On Repetitive Sequencesmentioning
confidence: 99%